Conceptual and methodological approaches and strategic for values education in school - Viteri Briones, Telmo (Revista Universidad de Guayaquil, 2010)
Our focus insists in the remanido matter of the conflict of securities. Synchronous voyage of an eventthat to be subject insertos in a social environment those “we value in fact”, and at the same time to possess a cultural cosmovisión we make it from those “you value of right.” Of another side it is a journey diacrónico, very shallow, of what School has been and he/she should make around this challenge in the desire of inaugurating a school work on habits valorativos in a community of critical, democratic, autonomous investigation, cooperative, equitable, respectful de/con its social and natural environments.
Keywords: Values: fact / law; emotional intelligence; cross-cutting themes: unitybiopsycho-social; meaningful learning